Features of the development of creative abilities aimed at developing the creative potential of students (Pedagogy of Higher and Secondary Education, 2011)
In the article examined main features of creative capabilities, as one of making elements of difficult integration personality-active description of man due to which, personality is carry out creative activity and the high level of development is arrived at.
Keywords: creative capabilities; creative personality